THE DIALECTIC OF GENDER AND RELIGIOUS AUTHORITY: THE CONSTRUCTION OF DISCOURSE ON WOMEN IN NING IMAZ'S DIGITAL DA'WAH - Hasyim, Nanang Mizwar (al-Balagh : Jurnal Dakwah dan Komunikasi, 2025)
Previous research on gender discourse in digital da'wah has not thoroughly analysed the mechanisms of gender discourse construction through a sophisticated critical discourse analysis approach on digital platforms. This study analyses the construction of women's discourse in Ning Imaz's digital da'wah on YouTube NU Online using Sara Mills' critical discourse analysis model on five da'wah videos from the 2022-2023 period. The findings reveal that Ning Imaz successfully builds personal religious authority through digital platforms, transforming the authority mechanism from a hierarchical-institutional model to a participatory-digital one. However, this discourse construction operates within the ‘Digital Islamic Feminism Paradox’—a fundamental dialectic between the empowerment and restriction of women through the naturalisation of the concept of ‘fitrah’ that legitimises gender hierarchy and the redefinition of terminology from “equality” to ‘gender justice.’ The transformation of digital religious authority does not result in radical gender emancipation but creates a space for negotiation that allows women to build influence while operating within theological boundaries. The implications are that female preachers need to develop more emancipatory discursive strategies, religious institutions must integrate critical gender perspectives, and audiences need to develop critical literacy for more progressive participation in the construction of contemporary religious meaning.